2022
DOI: 10.3390/foods11172598
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Key Aroma-Active Compounds in Two Types of Peach Spirits Produced by Distillation and Pervaporation by Means of the Sensomics Approach

Abstract: As a deep-processed product of peach, the aroma characteristics of peach spirit have not been systematically studied, and there has been no research on improving the aroma quality through process improvement. Pervaporation technology was used for the first time in the production of peach spirit instead of distillation, and its critical aroma compounds were analyzed compared with distilled peach spirit. Compared to the distilled peach spirit, pervaporation produced peach spirit presented stronger fruity, honey,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Aroma is very valuable for the consumer, and specific attention should be paid to odor-important compounds. Thus, if key odor-active compounds for peaches have to be identified, lactones will be among them [ 51 ]. Although past research [ 52 ] on the relative VOC concentrations and sensory attributes of peaches found higher concentrations of monoterpenes and esters compared to lactones in peaches, the latter are major contributors to the specific fruity, peach-like aroma [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aroma is very valuable for the consumer, and specific attention should be paid to odor-important compounds. Thus, if key odor-active compounds for peaches have to be identified, lactones will be among them [ 51 ]. Although past research [ 52 ] on the relative VOC concentrations and sensory attributes of peaches found higher concentrations of monoterpenes and esters compared to lactones in peaches, the latter are major contributors to the specific fruity, peach-like aroma [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once the alcohol content of the permeate in the feedstock tank reaches 0.5% vol or lower, a complete pervaporation process is completed. The initial pervaporation seizes the permeate, which serves as the raw material for the second pervaporation, ultimately resulting in peach spirit production exceeding 40% (v/v) (Wang et al., 2022). Figure 5a shows the process of producing fruit spirits using a single pervaporation membrane.…”
Section: Advanced Separation Technologymentioning
confidence: 99%
“…Furthermore, the pervaporation method has good separation efficiency for ethyl isobutyrate, isobutyl acetate, ethyl isovalerate, and ethyl hexanoate compared to that for Charentaise distillation, which facilitates the fruity property of the spirit. However, the quantity and content of terpenes are higher in the peach spirit produced using Charentaise distillation than in that produced via the pervaporation method (Wang et al., 2022). This result is due to the lack of high‐temperature heating in the pervaporation process because heating in distillation favors the accumulation of linalool and ( E )‐β‐damascenone (Kanasawud & Crouzet, 1990; Lukic et al., 2011; Wang et al., 2022; Yoshizaki et al., 2011).…”
Section: Advanced Separation Technologymentioning
confidence: 99%
See 2 more Smart Citations